Reconciling the role of terrestrial leaves in pond food webs: a whole‐ecosystem experiment - Meredith A. Holgerson; David M. Post; David K. Skelly (Ecology, 2016)
Terrestrial carbon and nutrients can subsidize the detrital pool of freshwater ecosystems; yet, the importance of terrestrial subsidies to lake and pond food webs is uncertain and debated. Terrestrial detritus is expected to have the greatest impact on food webs when water bodies are small and shallow with low levels of incident light. Temporary forested ponds fit this description and are often assumed to have a leaf detritus‐based food web, but this has not been quantified. In a whole‐ecosystem experiment, we traced the flow of isotopically enriched leaf litter to primary producers and consumers in a small, forested pond. We found that terrestrial leaves provided nutrients to algae, offering an indirect pathway in which leaf litter can enter the food web. Terrestrial leaves were also consumed directly, and larval caddisfly ( Limnephilus sp.) shredders likely mobilized leaf nutrients to other consumers, a process overlooked in many previous small‐scale experiments that did not incorporate shredders. Unexpectedly, most consumers relied heavily upon algal food pathways despite low light and net heterotrophic conditions. Overall, our study highlights the interconnectedness of algal and leaf litter pathways in small pond food webs, and emphasizes that algal pathways are prevalent and important even in small, shaded ponds with high loads of terrestrial leaf litter.